Antennas and Propagation - Tamas, Razvan D.; Badescu, Alina; Palade, Tudor; Alexa, Florin; Nicolaescu, Ioan (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue gathers topics of utmost interest in the field of antennas and propagation, such as: new directions and challenges in antenna design and propagation; innovative antenna technologies for space applications; metamaterial, metasurface and other periodic structures; antennas for 5G; electromagnetic field measurements and remote sensing applications.